Analisis Dampak Kecerdasan Buatan terhadap Epistemologis Pendidikan - Mulyani, Elis Karwati Sri; Nugraha, Mulyawan Safwandy (Jurnal Ilmiah Wahana Pendidikan, 2025)
The use of artificial intelligence (AI) in education has sparked discussion regarding its impact on the epistemological assumptions underlying the teaching-learning process. This study aims to analyze the impact of AI on educational epistemology, particularly in the development of critical thinking of junior high school students. The method used is a literature review with philosophical and technological approaches to explore the relationship between AI technology and epistemological assumptions. The results showed that AI, with its ability to process and present information, has the potential to change the epistemological approach from exploratory learning to more structured and data-driven. It is concluded that AI has significant implications for educational epistemology, necessitating adjustments in teaching methods to sustain the development of critical thinking.